Multiple Sclerosis and autoimmune diseases: clinical cases and review of the literature - G. Castellino; A. Protti; B. Canesi (PAGEPress Publications, 2001)
Multiple sclerosis (MS), the most frequent demyelinating disease in adults, is thought to be an autoimmune disease. Symptoms and signs observed in MS reflect lesions present mainly in the white matter of the central nervous system (CNS). The diagnosis remains difficult, at least concerning presenting symptoms, because of their low specificity. Diagnosis criteria are usually based on dissemination of signs in time and space, evoked potentials, findings of magnetic resonance imaging, results of cerebrospinal fluid examination, and the exclusion of other diagnosis possibly explaining the clinical signs. However, no clinical and paraclinical investigation can distinguish with certainity MS from other conditions such as autoimmune or inflammatory diseases predominantly affecting the central nervous system. These other disorders include systemic lupus erythematosus, antiphospholipid syndrome, Behcet disease, Sjogren syndrome, sarcoidosis and vasculitides. We present four clinical cases showing the difficulty in reaching a proper diagnosis...